Effects of vertical and horizontal plyometric exercises on explosive capacity and kinetic variables in professional long jump athletes - Vazini Taher, A.; Pavlovic, R.; Ahanjan, S.; Skrypchenko, I.; Joksimovic, M. (Pedagogy of Physical Culture and Sports, 2021)
Background and Study Aim. Athletic jumps are specific cyclically-acyclic movements that despite the good performance of the techniques require from competitors a high level of motor, specific-motor and functional abilities. The aim of this study was to examine the response effect of vertical and horizontal plyometric training on explosive capacity and kinetic variables in long jump athletes. Material and Methods. The participants of this study were twenty professional jumpers (22.5 ± 4.2 years; 178.4 ± 9.8 cm; 70.3 ± 7.6 kg) who were divided into two groups: experimental (plyometric training) and control (standard training). They participated in the last track and field championship in country, moreover, three of them participated in the last Asian games, and one athlete participated in the world track and field championship. The experiments were conducted on June-July 2019 in twenty professional athletes. All tests were performed after a standard warm up protocol. The place of camera was always determined wisely around the jumping field to attain best photography. Organizing and controlling the imaging and motor analysis processes were done by a biomechanics expert. Results. Post training results in experimental group showed more improvement in 30 m sprint, vertical jump, horizontal velocity at take-off, and long jump completion, comparing the control group. Significant between group differences in all variables were detected post training. No significant post training improvements in flight time and take off duration were reported in control group. Conclusion. Vertical and horizontal plyometric training protocol was shown to be more effective in promoting improvement in explosive capacity than kinetic variables.